Development of a real-time algorithm for detection of the divertor detachment radiation front using multi-spectral imaging. (5th May 2020) - Ravensbergen, T.; van Berkel, M.; Silburn, S.A.; Harrison, J.R.; Perek, A.; Verhaegh, K.; Vijvers, W.A.J.; Theiler, C.; Kirk, A.; de Baar, M.R.; the EUROfusion MST1 team
Abstract: In this paper we present a novel algorithm to extract the optical plasma boundary and radiation front for detached divertor plasmas. We show that reliable detection of the divertor leg and radiation front is possible using lightweight image processing tools. Using a non-tomographic approach, the detected divertor leg and radiation front can be mapped to the poloidal plane. This approach is fast and accurate enough for real-time control purposes, allowing in particular real-time plasma shape and detachment control, and post-shot detachment physics and dynamics analysis.